Pathological alterations associated with mandibular third molars: a clinical, radiographic and histopathological study - Silveira, Rubens Jorge; Cascaes, Paula de Sousa Lopes; Oenning, Anne Caroline; Dorta, Regina; Botelho, Tessa; Junqueira, José Luiz; Soares, Mariana Quirino Silveira (Brazilian Dental Science, 2026)
Objective: Radiographic examination is routinely performed to detect pathoses associated with impacted teeth; however, evidence suggests that pathological alterations may occur in asymptomatic dental follicles exhibiting normal radiographic features. This study aimed to evaluate the presence of pathological changes in pericoronal follicles of unerupted mandibular third molars without radiographic evidence of associated lesions. Material and Methods: Patients indicated for surgical removal of mandibular third molars without evident clinical or radiographic abnormalities were included. Clinical and intraoperative data regarding sex, age, pain, gingival coverage, and distal bone loss of adjacent second molars were recorded. Radiographs were assessed for tooth position, impaction pattern, and root resorption. All pericoronal follicles were submitted to histopathological examination to identify cystic changes, epithelial lining characteristics, and inflammatory infiltrate. Results: The sample comprised 49 patients and 73 unerupted or partially erupted mandibular third molars. Histopathological analysis revealed 45.2% normal follicles, 28.8% dentigerous cysts, and 26.0% paradental cysts. An epithelial lining was identified in 56.2% of specimens, predominantly stratified squamous epithelium (82.9%). Inflammatory infiltrate was present in 64.4% of cases and was significantly more frequent in teeth partially covered by gingival tissue. No significant associations were observed with sex or age. Conclusion: A substantial proportion of pericoronal follicles exhibited pathological alterations despite the absence of clinical or radiographic signs of disease. These findings underscore the value of histopathological evaluation in supporting clinical decision-making regarding monitoring or removal of impacted mandibular third molars in selected cases. KEYWORDS Histology; Mandibular third molar impacted; Pathology; Radiography.